Stunting dan Ketahanan Keluarga, Desa Giripawana Kec. Mandalawangi, Pandeglang Banten - Aisyah Putri Fadillah; Handewi Ayu Pramesti; Rival Hajronal Qudsi; Naf'an Tarihoran (Lembaga Pengembangan Kinerja Dosen, 2024)
Stunting is a growth disorder caused by a long-term lack of nutrition, starting during pregnancy and continuing until the child reaches the age of 24 months. This condition is a serious problem that is associated with an increased risk of various health problems, such as disease, premature death, and delays in children's motor and mental development. Stunting can significantly hinder a child's physical and cognitive development, which ultimately has a negative impact on their quality of life in the future. To overcome the problem of stunting, this program was designed with the main aim of increasing community awareness in Giripawana village regarding the importance of healthy living habits as a measure to prevent stunting. This program focuses on educating the public, especially teenagers, about the importance of good nutrition from an early age and the negative impact of early marriage which can reduce the risk of stunting. Apart from that, this program also involves consultation with parents regarding the causes of stunting, the possible impact on children's health and development, as well as preventive steps that can be taken. The education provided covers various aspects such as good parenting patterns and choosing nutritious foods which are very important to support children's optimal growth. Research conducted in Giripawana village used a phenomenological approach with qualitative methods to further explore the experiences and factors that influence stunting in the community. This research involved 25 toddlers who were classified as high risk of stunting. However, the evaluation results showed that only 2 toddlers actually experienced stunting. This research aims to understand in depth the lived experiences and perspectives of families and communities regarding the problem of stunting, as well as to assess the effectiveness of education and intervention programs that have been implemented. Using a phenomenological approach, this research seeks to explore the subjective experiences of families and communities regarding stunting, to gain a more comprehensive insight into this problem. It is hoped that the results of this research will provide valuable information that can be used to plan and implement more effective stunting prevention and control programs in the future, as well as to improve the quality of life of children in the community.The research results show that most of the health problems in Giripawana village are caused by malnutrition in children under five, which often ends in stunting. We strongly believe that through this outreach, community awareness in Giripawana village will increase regarding the importance of maintaining the health and nutrition of their children. The important role of parents, especially mothers, is in ensuring that their children receive adequate and balanced nutritional intake. The importance of early detection of signs of stunting so that appropriate intervention can be carried out as early as possible.